Creative use of Clear Aligners with Tongue Spikes for Open Bite Correction: A Case Report - Ricardo Alexandre Laske; Rosilene Andrea Machado; Gil Guilherme Gasparello; Thiago Martrtins Meira; Orlando Motohiro Tanaka (Journal of Clinical and Diagnostic Research, 2025)
Anterior Open Bite (AOB) is a complex dental condition caused by a variety of factors, including genetics, environmental influences, and functional issues. Managing AOB presents considerable challenges due to the high likelihood of relapse, particularly in cases linked to tongue dysfunction. Accurate diagnosis and thorough treatment planning are essential, especially when addressing factors such as tongue posture, which impacts speech, swallowing, and chewing. Achieving and maintaining an ideal overbite is particularly challenging, making it one of the most difficult aspects of orthodontic treatment. This case report demonstrates the effectiveness of using clear aligners with sharpened tongue spurs to address orthodontic relapse, misalignment, and AOB in an adult female patient. The application of a mandibular clear aligner combined with a tongue spike successfully treated the AOB caused by the patient’s tongue rest posture, leading to improved aesthetics, function, and patient satisfaction. The patient’s compliance with the aligner and adherence to proper tongue posture were crucial, similar to the requirements when using Temporary Anchorage Devices (TADs), multiloop archwires, and vertical elastics. Strict adherence to the clear aligner regimen was essential for achieving favourable results. Additionally, while it is generally recommended to consult with a myofunctional therapist before and during orthodontic treatment, in this case, the patient did not attend any such consultations. By combining functional effectiveness with a minimally invasive, aesthetic, and patient-centred approach, this method provides a valuable option for managing AOB associated with abnormal tongue posture. The results from this case highlight the potential for integrating innovative techniques into clear aligner therapy to achieve optimal outcomes in adult orthodontic treatments.